2019
DOI: 10.1002/ijc.32521
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma‐derived extracellular vesicles instigate proinflammatory signaling in the metastatic microenvironment

Abstract: The major cause of melanoma mortality is metastasis to distant organs, including lungs and brain. Reciprocal interactions of metastasizing tumor cells with stromal cells in secondary sites play a critical role in all stages of tumorigenesis and metastasis. Changes in the metastatic microenvironment were shown to precede clinically relevant metastases, and may occur prior to the arrival of disseminated tumor cells to the distant organ, thus creating a hospitable “premetastatic niche.” Exosomes secreted by tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 49 publications
0
48
0
Order By: Relevance
“…Several studies demonstrate roles in tumorigenesis for other EV cargo types, including mRNA and lncRNA. Indeed, melanoma cell-derived EVs exhibited differential expression of over 1600 transcripts when compared to fibroblast-derived EVs, suggesting an important role for mRNA incorporation into EVs [138]. Specific mRNAs, including those encoding TNF-α, TGF-β, and IL-6, have been found to be transferred from cancer cells to fibroblasts and to regulate fibroblast differentiation and function [130].…”
Section: Other Cargos (Mrna and Lncrna)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrate roles in tumorigenesis for other EV cargo types, including mRNA and lncRNA. Indeed, melanoma cell-derived EVs exhibited differential expression of over 1600 transcripts when compared to fibroblast-derived EVs, suggesting an important role for mRNA incorporation into EVs [138]. Specific mRNAs, including those encoding TNF-α, TGF-β, and IL-6, have been found to be transferred from cancer cells to fibroblasts and to regulate fibroblast differentiation and function [130].…”
Section: Other Cargos (Mrna and Lncrna)mentioning
confidence: 99%
“…As a result, the activated fibroblasts secrete pro-inflammatory cytokines and promote metastatic cancer growth [172]. Furthermore, EVs secreted by metastatic melanoma cells induce a pro-inflammatory profile in lung fibroblasts without any differences in wound healing functions, while also triggering pro-inflammatory signaling in astrocytes [138].…”
Section: Evs and Pre-metastatic Niche Formationmentioning
confidence: 99%
“…Cancer cells educate fibroblasts through EVs, which leads to the progression of metastasis [ 48 ]. Cancer-derived EVs are involved in the reprogramming of normal stromal fibroblasts into activated cancer-associated fibroblasts (CAFs) in chronic lymphocytic leukemia [ 49 ], hepatocellular carcinoma (HCC) [ 50 ], and melanoma [ 51 ]. These studies revealed that the CAF transition leads to metastatic niche formation and promotes cancer metastasis.…”
Section: Function Of Evs In Cancer Metastasismentioning
confidence: 99%
“…For example, astrocytes-derived exosomes enriched with miR-19a may increase brain cancer metastasis by increasing the loss of phosphatase and tensin homolog (PTEN) in tumor cells and C-C motif chemokine ligand 2 (CCL2) chemokine secretion ( Zhang et al, 2015 ). Melanoma cells secrete EVs which can activate pro-inflammatory signals in astrocytes and promote metastasis and tumor formation ( Gener Lahav et al, 2019 ). Glioma-derived EVs increase inhibition of TP53 and MYC signaling pathway activation in astrocytes.…”
Section: Astrocytes Evs and Cns Diseasesmentioning
confidence: 99%